PENGEMBANGAN MEDIA PEMBELAJARAN BOARD GAME MATEMATIKA KELAS VIII SEMESETER 1 KURIKULUM 2013 DI SMP NEGERI 48 JAKARTA - DANANG HADI NUGROHO (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2021)
The development of the world of technology at this time has an influence and impact. The objectives of this research are (1) To produce a board game media product for mathematics, the subject matter of semester 1 of the 2013 curriculum for class VIII students of SMP Negeri 48 Jakarta. (2) To determine the effectiveness of the board game media product, the subject matter of the first semester of the 2013 curriculum for class VIII students of SMP Negeri 48 Jakarta. The development model used is the Research and Development (R&D) model because R&D development has more systematic and detailed steps at each stage. The data analysis technique in this study used a questionnaire, structured interviews and tests to determine the feasibility of the media. To determine the level of effectiveness using the t test analysis technique while for the feasibility of the Guttman analysis technique. The product feasibility data is determined through the analysis of the results of the validation of the material expert 100% which is included in the very good category, the media expert is 93.33% which is also included in the very good category, the learning design expert is 87.5% which is included in the very good category. good, the expert of the accompanying material is 95% which is included in the very good category. The trials that were carried out were both individual trials assessed that 91.11% was included in the very good category, small group trials assessed 83.33%, while large group trials were 94.4% and all were included in the very good category. From all the assessments and categories that have been assessed, it can be concluded that the development of a mathematical board game for the first semester of the 2013 curriculum for class VIII students of SMP Negeri 48 Jakarta, is suitable for use by students. and media experts as well as individual product trials, small groups, and large groups get a very good category, so that the board game media is feasible to be applied in learning mathematics, the subject matter of semester 1 class VIII curriculum 2013 in everyday life. Meanwhile, the results of the t-test data analysis and the researcher can conclude that the average result of the posttest trial is 83.52, which is higher than the average result of the pre-test, which is 56.17. Through the t-test calculation, it is known that the t-count result is 15.337. In addition, based on testing using a significant level of 5% db = 34-1 = 33, it was obtained ttable = 2.034. So the researcher can conclude that tcount is greater than ttable, namely 15.337 > 2.034. So that there is a significant difference between the pre-test and post-test and it can be concluded that the board game media is effectively used in learning mathematics for the first semester of the 2013 curriculum for class VIII students of SMP Negeri 48 Jakarta. ABSTRAKPerkembangan dunia teknologi pada saat ini memberikan pengaruh serta dampak yang Tujuan dari penelitian ini adalah (1) Menghasilkan produk media board game matematika materi pokok semester 1 kurikulum 2013 untuk peserta didik kelas VIII SMP Negeri 48 Jakarta. (2) Mengetahui keefektifan produk media board game matematika materi pokok semester 1 kurikulum 2013 untuk peserta didik kelas VIII SMP Negeri 48 Jakarta. Model pengembangan yang digunakan adalah model Reseach and Development (R&D) karena pengembangan R&D memiliki langkah-langkah yang lebih sistematis dan terperinci disetiap tahapannya. Teknik analisis data pada penelitian ini menggunakan angket, wawancara terstruktur dan tes untuk mengetahui kelayakan media. Untuk mengetahui tingkat efektifitas menggunakan teknik analisis uji t sedangkan untuk kelayakan teknik analisis guttman. Data kelayakan produk yang dihasilkan, ditentukan melalui analisis hasil validasi ahli materi 100% yang termasuk dalam kategori sangat baik, ahli media yaitu 93,33% dimana juga termasuk dalam kategori sangat baik, ahli desain pembelajaran yaitu 87,5% yang termasuk dalam kategori sangat baik, ahli bahan penyerta yaitu 95% yang termasuk dalam kategori sangat baik. Uji coba yang dilakukan baik uji coba perorangan menilai 91,11% termasuk dalam kategori sangat baik, uji coba kelompok kecil menilai 83,33%, sedangkan uji kelompok besar 94,4% dan semua termasuk dalam kategori sangat baik. Dari semua penilaian dan kategori yang sudah dinilai maka dapat disimpulkan bahwa Pengembangan board game matematika materi pokok semester 1 kurikulum 2013 untuk peserta didik kelas VIII SMP Negeri 48 Jakarta, layak untuk digunakan oleh peserta didik. dan ahli media serta uji coba produk perorangan, kelompok kecil, hingga kelompok besar mendapatkan kategori yang sangat baik, sehingga media board game layak untuk diterapkan dalam pembelajaran matematika materi pokok semester 1 kelas VIII kurikulum 2013 dalam kehidupan sehari-hari. Sedangkan hasil analisis data uji t dan peneliti dapat menyimpulkan bahwa hasil rata-rata uji coba posttest yaitu 83,52 lebih tinggi dibandingkan dengan hasil rata-rata pre-test yaitu 56,17. Melalui perhitungan uji t diketahui hasil thitung sebesar 15,337. Selain itu, berdasarkan pengujian menggunakan taraf signifikan 5% db = 34-1 = 33 diperoleh ttabel = 2,034. Jadi peneliti dapat menyimpulkan bahwa thitung lebih besar dari ttabel yaitu 15,337 > 2,034. Sehingga terjadi perbedaan yang signifikan antara pre-test dan post-test dan dapat disimpulkan bahwa media board game efektif digunakan pada pembelajaran matematika materi pokok semester 1 kurikulum 2013 untuk peserta didik kelas VIII SMP Negeri 48 Jakarta.